Bacterial contamination of surgical instruments in 25-gauge pars plana vitrectomy: Incidence and risk factors - Fumiya Miyako; Yosuke Harada; Tomona Hiyama; Seiya Kashiyama; Saori Kawamoto; Chika Yokota; Akira Minamoto; Hiroki Ota; Ayako Sadahide; Kazuyuki Hirooka; Taiichiro Chikama; Hirokazu Sakaguchi (PLoS ONE, 2026)
Purpose To evaluate the incidence of surgical instrument contamination associated with microincision vitrectomy surgery. Methods Ninety-six eyes from 86 immunocompetent patients who underwent 25-gauge pars plana vitrectomy from December 2023 to February 2024 in our institution were retrospectively analyzed. Results Surgical instrument contamination was detected in 7 cases (7.3%). Bacterial species were isolated from the trocar, endoilluminator, and beveled probe. Postoperative endophthalmitis did not occur during the 2-month follow-up period. Use of preoperative antibacterial eye drops was significantly associated with lower risk of bacterial contamination. Conclusion Contamination may occur 25-gauge pars plana vitrectomy, even when preoperative antibacterial eye drops are used in conjunction with povidone-iodine irrigation and adequate vitreous dissection.